MO693EXERCISE TOLERANCE AND NUTRITIONAL STATUS PREDICTS ALL-CAUSE MORTALITY IN OLDER ADULTS ON PERITONEAL DIALYSIS: A SINGLE-CENTER PROSPECTIVE OBSERVATIONAL COHORT STUDY. (29th May 2021) - Yabe, Hiroki; Imoto, Yuto; Ito, Sayaka; Onoyama, Ayaka; Okada, Keiko; Kasuga, Hirotake
Abstract: Background and Aims: Peritoneal dialysis (PD) is beneficial for older adults with end-stage renal disease (ESRD) because it allows for dialysis treatment in their own homes. The risk factors associated with specific prognoses in elderly PD patients need to be explored to continue stably without adverse events. However, the risk of adverse events specific to older adults on PD has not been thoroughly investigated. The critical risk factor for ESRD and aging is decreased physical function. The purpose of this study was to assess the association between physical function and outcomes in older adults on PD. Methods: This was a single-center, prospective observational cohort study. Stable, ambulatory patients undergoing PD between April 1, 2014, and September 31, 2016, were enrolled. Six-minute walk distance (6MWD), short physical performance battery (SPPB), lower extremity muscle strength (LES), and 10-meter walk speed were measured for each patient. Laboratory data were also collected. All subjects were followed up until death or the end of the follow-up period (December 31, 2019). This ethical institution at the Seire Christopher University approved all procedures performed in this study. Informed consent was obtained from all the patients. Baseline patient characteristics and physical function were compared using an unpaired t-test or Mann-Whitney U test. Receiver operating characteristic curve analysis on mortality prediction was performed to calculate the area under the curve in the significant value of the unpaired t-test or Mann-Whitney U test. We used the Youden index to determine the optimal cut-off point, and patients were categorized into 2 groups by each cut-off value. The relationship between all-cause mortality and each variable was studied using Kaplan-Meier analysis and the log-rank test. All tests were assessed at a statistical significance of p<0.05. Results: Thirty-seven patients were enrolled. Three patients refused to participate in the study, and one patient was excluded because they had a medical reason. Therefore, 33 patients (age: 74.8 ± 5.9 years) were finally included in the present study. The median follow-up time was 39 months (interquartile range: 28–49 months), during which 19 (57.6%) deaths occurred. Death during follow-up was significantly associated with lower 6MWD (234.6.9±115.8 vs. 351.9±105.8 m), lower serum albumin (Alb, 2.7±0.6 vs. 3.2±0.4 mg/dL), and lower Geriatric Nutritional Risk Index (GNRI, 79.7±9.9 vs. 88.5±7.1) than those who did not die (died vs. not died group, respectively). No other variables were significantly different between the groups. The cut-off value, discriminating those at high risk of mortality, for the 6MWD was 338m, Alb was 3.0 ml/dL, and GNRI was 83.7. In the Kaplan-Meier survival analysis and log-rank test, 6MWD, Alb, and GNRI were significantly associated with all-cause mortality. Conclusion: This is the first study, to our knowledge, to show that lower 6MWD scores were associated with all-cause mortality in older adults on PD, suggesting that objective exercise tolerance measures may be useful for the risk stratification of older adults undergoing PD. Although the results were obtained from a small sample size, this study has clinical significance because older adults on PD are rare. The 6MWD is a useful measurement that reflects exercise tolerance, has good reliability, has low cost, and is easily applicable. The results of this study support those of previous studies in other groups showing that 6MWD and nutritional status significantly predicted prognosis. Therefore, low exercise tolerance and malnutrition may represent an important therapeutic target in this population.